THE EFFECT OF MATCH MINE TECHNIQUE ON STUDENTS’ SPEAKING SKILL (A Pre-Experimental Study at the Tenth Grade Students of Senior High School 10 Kendari) - Arwa, Arwa; Suhartini, Lelly; Muhsin, Muhammad Khusnun (Journal of Teaching of English, 2020)
This study was conducted to examine whether there is any significant effect of Match Mine technique on students’ speaking skill at the tenth grade students’ of Senior High School 10 Kendari. This research was conducted in a pre-experimental research design. The population of this research was all the first grade science program students (X MIPA) of Senior High School 10 Kendari. The total population was 104 students which consisted of four classes. The sample of this research was the first-grade science program students (X MIPA 1) which consisted of 22 students. The data of this research were collected by giving the students pre-test and post-test in the form of oral test that related to the topic of Descriptive text (describe people and things). Then, the data were analyzed by using SPSS 16.0 version by using (descriptive analysis and inferential statistics). The descriptive analysis used for describing the data of this study, such as the mean score, median, standard deviation, the maximum scores, and the minimum scores. While inferential statistics used to examine the hypothesis of this study (H1). For testing the hypothesis of this study, the researcher used a paired sample t-test which was calculated through SPSS 16.0. The result shows that there is a significant effect of Match Mine technique on students’ speaking skill at the tenth grade students of Senior High School 10 Kendari. It can be seen at the mean score of post-test. The mean score of post test is 53.64, while the mean score of pre-test is 31.14. In order to prove the hypothesis, the researcher compares the value of Sig (2 tailed) with the significance α value. In this study, the value of Sig (2 tailed) is 0.000 while the significance α value is 0.05. Thus, it can be concluded that the value of Sig (2 tailed) is lower than the significance α value (0.000 < 0.05). In other words, (H1) is accepted. It means that there is a significant effect of Match Mine technique on students’ speaking skill at the tenth grade students of Senior High School 10 Kendari. In addition, the student’s speaking accuracy and fluency are better than before. Furthermore, the result of the finding above also shows that Match Mine technique can affect students’ motivation and communicative skill and the result of the finding also can be affected by students’ intelligence itself.